PEMBAHARUAN PENGATURAN TINDAK PIDANA PERKOSAAN DALAM UNDANG-UNDANG NOMOR 1 TAHUN 2023 (ANALISIS KESESUAIAN KEBUTUHAN HUKUM DI INDONESIA) - Nur Muhammad Ikhsan; Eza Aulia (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
Rape constitutes one of the most serious forms of sexual violence, as it directly violates human dignity, personal autonomy, and fundamental human rights. In Indonesia, the regulation of rape was historically governed by Article 285 of the Criminal Code inherited from the colonial era, which narrowly defined rape as sexual intercourse committed by a man against a woman outside marriage through violence or threat. This formulation was increasingly considered inadequate to address contemporary social realities, including diverse forms of sexual violence, male victims, and sexual coercion within marital relationships. In response to these shortcomings, Indonesia enacted Law Number 1 of 2023 on the Criminal Code, introducing significant reforms to the regulation of rape.This study aims to analyze whether the reformed regulation of rape under Law Number 1 of 2023 is consistent with the legal needs of Indonesian society. The research employs a normative juridical method, focusing on doctrinal legal analysis through statutory and conceptual approaches. The study examines primary legal materials in the form of legislation, supported by secondary legal materials such as legal doctrines, scholarly books, academic journals, and purposively selected expert opinions from criminal law scholars.The findings reveal that the reformulation of rape, particularly the expansion of the victim’s subject from “a woman” to “any person,” represents a progressive shift toward a victim-oriented and inclusive criminal law policy. This development aligns with the principles of justice, utility, and legal certainty as articulated in Gustav Radbruch’s theory of legal objectives, and reflects a stronger commitment to human rights protection and equality before the law. However, the recognition of rape within marriage, as regulated in Article 473 paragraph (2)(a), remains controversial. Although normatively intended to protect victims, this provision raises significant challenges related to evidentiary standards, legal certainty, and compatibility with prevailing social, cultural, and religious values. Consequently, while the reform generally moves in the right direction, further refinement is required to ensure effective implementation, proportional criminalization, and balanced protection of legal interests within Indonesian society.